Consumer perception and use intention for household distributed photovoltaic systems. (June 2022) - Zhang, Wan-Hao; Chou, Li-Chen; Chen, Mengdi
Abstract: Given the importance of promoting renewable energy, the Chinese government has enacted policies to encourage residents to install and use household distributed photovoltaic (PV) systems. However, only a few studies investigated factors influencing residents' use intention for household PV systems. The present study therefore investigated the influence of Chinese residents' environmental concern and innovativeness on their use intention for household PV system, as well as the mediating effects of perceived benefits and harm of household PV system in this process. Furthermore, the moderating role of residents' monthly electricity consumption in the above-mentioned association was also examined. Questionaire data from 400 Chinese participants in Zhejiang Province were used for analysis. Results from structural equation modeling suggested positive associations between environmental concern and use intention, and between innovativeness and use intention, through the mediating of perceived benefits and harm. Residents' monthly electricity consumption also moderate part of the associations. Based on the results, this paper calls on the government to regulate the safety standard of household PV nationwide to enhance social confidence. Conspicuous consumption, which comes with "traditional customs", should also be reduced.